The Effect of Influencer Credibility and Celebrity Endorsements on Purchase Intention, with E-Trust as a Mediating Variable - Kelvin Setiawan; Michael Christian (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The rapid growth of digital marketing has transformed the way consumers interact with brands, particularly through the use of influencers and celebrity endorsements. However, the effectiveness of these strategies largely depends on the level of trust consumers develop in digital environments (e-trust). This study aims to analyze the effect of influencer credibility and celebrity endorsement on purchase intention, with e-trust as a mediating variable. This research adopted a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through a structured questionnaire using a Likert scale and analyzed to examine both direct and indirect relationships among variables. The results indicate that influencer credibility and celebrity endorsement have a positive and significant effect on e-trust. Furthermore, both variables also significantly influence purchase intention. E-trust is proven to have a positive effect on purchase intention and partially mediates the relationship between influencer credibility and celebrity endorsement with purchase intention. The structural model demonstrates strong predictive power and reliability. In conclusion, the effectiveness of influencer and celebrity-based marketing strategies is significantly enhanced when they are able to build consumer trust. Therefore, companies should prioritize selecting credible influencers and trustworthy endorsers to strengthen e-trust and increase consumer purchase intention